The danger of a single story: Iconic stories in the aftermath of the 1994 Rwandan genocide. (April 2017) - Jessee, Erin
In the aftermath of the 1994 genocide, the government of Rwanda—much like other transitional regimes around the world—has prioritized reconciliation initiatives that educate civilians with a highly politicized understanding of the conflict and encourage them to speak about the conflict and its aftermath in a manner that reinforces the legitimacy of the current government. However, individual survivors, bystanders, ex-combatants, and/or perpetrators of the genocide find various subtle ways to reinforce, resist, or complicate the current official history. This article analyzes a series of "iconic stories" that are repeated by Rwandans in different settings due to their historical and personal resonance for what they can tell us about the ethnic and political tensions that often continue to divide Rwandans and the overall challenges associated with everyday life since the genocide. Yet, engaging with these iconic stories places the researcher in a difficult position where the democratizing potential of oral history is potentially undermined. This article argues that even while qualitative researchers have an obligation to listen deeply to their informants, their moral and professional obligations to avoid reproducing narratives that promote potentially reprehensible agendas—for example, genocide denial or the legitimation of authoritarianism—make contextualizing their participants' narratives in relation to the personal, historical, and political climate in which they are being produced essential.